Depression as Predictor of Self-Injurious Behavior among Individual Living in Shelter Homes: Moderating Role of Attribution Style - Warda Sadiq; Dr. Sher Dil (Journal of Religion and Society, 2025)
Depression is a serious condition that impact the way individual react to the situation. One of the leading consequences of depression is non-suicidal self-injurious behavior. The literature has documented the impact of negative attribution on depression as well as non-suicidal self-injurious behaviors. The current study aimed to examine how depression influence the occurrence of non-suicidal self-injurious behaviors and how negative attribution style moderated the relationship between depression and non-suicidal self-injurious behaviors among residents of shelter homes. A sample of 300 residents of shelter homes was approached individually and three questionnaires were used for the data collection, attributional style questionnaire, Zung self- rating depression scale and Ottawa self- injury inventory along with demographic sheet. The result analysis revealed a positive correlation among self-injurious behavior, depression, and negative attributional style. The results revealed that depression is significant predictor of self-injurious behavior. Negative attributional style significantly moderated the relationship between depression and self-injurious behavior. Keywords: Depression, Predictor, Self-Injurious, Behavior, Individual Living, Shelter Homes